[(x*2+3)*4:5+6]+7-8=9
Răspunsuri la întrebare
Răspuns de
1
(x*2+3*4:5+6)+7=17
x*2+3*4:5+6=10
x*2+2,4+6=10
x*2+2,4=4
x*2=1,6
x=0,8
sper că te-am ajutat
x*2+3*4:5+6=10
x*2+2,4+6=10
x*2+2,4=4
x*2=1,6
x=0,8
sper că te-am ajutat
Răspuns de
5
[(x*2+3)*4:5+6]+7-8=9
[(x*2+3)*4:5-5]+7=8+9
[(x*2+3)*4:5-5]+7=17
(x*2+3)*4:5-5=17-7
(x*2+3)*4:5-5=10
(x*2+3)*4:5=5+10
(x*2+3)*4:5=15
(x*2+3)*4=15*5
(x*2+3)*3=75
x*2+3=75:3
x*2+3=25
x*2=25-3
x*2=22
x=22:2
x=11
[(x*2+3)*4:5-5]+7=8+9
[(x*2+3)*4:5-5]+7=17
(x*2+3)*4:5-5=17-7
(x*2+3)*4:5-5=10
(x*2+3)*4:5=5+10
(x*2+3)*4:5=15
(x*2+3)*4=15*5
(x*2+3)*3=75
x*2+3=75:3
x*2+3=25
x*2=25-3
x*2=22
x=22:2
x=11
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Engleza,
9 ani în urmă
Engleza,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă